Status of Financial Literacy Centers in Karnataka - Sangeetha, R; Mathew, Jain; Francline, Sheethal C (Ushus Journal of Business Management, 2017)
Financial literacy as a key pillar for a better financial system, helps to improve the financial situation of the citizens by achieving higher economic growth. This study aims to find out the status of Financial Literacy Center, among 30 districts in Karnataka over a period of 9 years (2008-2009 to 2016-17). The variables considered for the study are Deposits, Advances, Credit Deposit Ratio (CD ratio), Financial Literacy Centers (FLC) and Number of Reporting Offices (no. of reporting offices) available in the district. Data has been collected from various secondary sources like RBI, SLBC, Data Base on Indian Economy, etc., and analyzed using Descriptive statistics, Regression and ANOVA. It is found that there is an impact of FLC on CD ratio. However growth of the CD ratio is not in alignment with the growth in FLC.